Manufaktur Paku Beton Diameter 4 mm, Panjang 50 mm, Kapasitas 100 Biji/Jam - Idodim Fajar; Syamsul Hadi; M. Taufik; Zulfiqin Zaki Askari; Achmad Yulianto; Dzaky Fatwa Adibya Sufi (International Forum of Researchers and Lecturers, 2026)
The ease of bending of nails when hammered into the cement concrete surface is a problem encountered in the field. The manufacturing objective is to obtain concrete nails with a diameter of 4 mm, a length of 50 mm that do not bend when hammered into the cement concrete surface. The manufacturing method includes: design of concrete nails with a diameter of 4 mm, a length of 50 mm; selection including the purchase of medium carbon steel, AISI 1045; straightening and reducing the wire rod (wire drawing) from a diameter of 10 mm to a diameter of 4 mm with 6 stages of reduction; cold forming (cold heading) of AISI 1045 material to form the nail head; cutting into the shape of the nail tip; and checking the quality-dimensions of the nails. The manufacturing results are concrete nails with a diameter of 4 mm, a length of 50 mm that do not bend easily when hammered into the cement concrete surface with a production cost of Rp 450,-/piece and a production duration of 45 seconds/piece which consequently means that the concrete nails can be nailed into the cement concrete surface without bending and can be produced on a small to medium industrial scale.